Future story with Madam Haliza Yahaya / Nazira Jamil and Nur Farahin Zolkarnain - Jamil, Nazira; Zolkarnain, Nur Farahin (Faculty of Information Management, 2015)
The main theme of this article is about Information Professional (IP). IP is an individual who organize, store and disseminate information to potential users. They also have known as a group of people who work in the information industry to provide the reliable and authentic information. This group of people usually refers to the librarian, information resources officer, and information management lecturer. The phrase 'librarians and information professionals" refers to members of the profession whose has completed an entry-level qualification in library and information management at either Associate or Library Technician level (Australian Library and Information Association).